The scarlet thread of scandal morality and the American presidency - Dunn, Charles Wesley 1885- (Rowman & Littlefield, 2000)
Scandals are surely nothing new in the White House--ever since the creation of the republic, presidents have made morally questionable judgments, whether constitutional, ethical, legal, or personal. In eloquent and judicious prose, Dunn chronicles the numerous controversies in presidential history, paying particular attention to their impact on the American people and public memory. The Scarlet Thread of Scandal will make all Americans think differently about past, present, and future presidents.